Creative Economy Potential Analysis for Increasing Community Income of Noken Craftswomen in Mimika - Menas Mayau; J Ary Mollet; Transna Putra Urip (Jurnal Bisnis dan Pemasaran Digital, 2026)
Purpose: This study examines income levels of noken bag craftswomen in Mimika Baru District, Mimika Regency, Papua, and identifies internal and external factors that support or hinder this creative economy activity, along with strategies for raising craftswomen income.Research Methodology: A quantitative descriptive approach used 27 noken craftswomen selected through purposive sampling as key informants, with data collected through questionnaires, observation, and documentation, analyzed using production cost and revenue calculations together with Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis supported by Internal and External Factor Analysis Summary matrices.Results: Average production cost per cycle was IDR 547,963, average total revenue reached IDR 4,617,308, yielding average net income of IDR 4,070,769. Nylon-yarn noken generated higher revenue, IDR 2,544,231, than wool-yarn noken, IDR 2,073,077, though both sold at the same unit price of IDR 350,000. Internal analysis produced a strength score of 2.05 against a weakness score of 1.87, while external analysis produced a threat score of 2.60 against an opportunity score of 1.46, positioning craftswomen in the aggressive growth quadrant with an Strenght and Oportunities (SO) strategy orientation.Conclusions: Noken craftswomen occupy a financially productive but structurally vulnerable position favoring strength-based expansion strategies.Limitations: The purposive sample of 27 respondents restricts generalization beyond Mimika Baru District.Contributions: The study offers empirically grounded income figures and a strategy framework local government and cooperatives can use for targeted noken empowerment programs.